HemosIL VWF:GPIbR Assay Has a Greater Sensitivity than VWF:RCo Technique to Detect Acquired von Willebrand Syndrome in Myeloproliferative Neoplasms - Laporte, Pierre; Tuffigo, Marie; Ryman, Anne; Fiore, Mathieu; Rivière, Etienne; James, Chloé; Guy, Alexandre (Thrombosis and Haemostasis, 2022)
Background Acquired von Willebrand syndrome (AVWS) is frequent in patients with myeloproliferative neoplasms (MPNs). For von Willebrand factor (VWF) functional evaluation, ristocetin cofactor activity by aggregometry (VWF:RCo) is considered the gold standard but has limitations, and automated activity measurement has been developed such as the HemosIL VWF:RCo Werfen with particle agglutination (VWF:GPIbR).Objectives To evaluate the performance of VWF:GPIbR with HemosIL VWF:RCo Werfen (VWF:GPIbR) versus VWF:RCo in patients with thrombocytosis in the context of MPNs (T-MPNs) and in patients with secondary thrombocytosis (ST).Methods MPN patients with thrombocytosis >450 G/L (T-MPNs) were compared with patients with ST due to inflammation or iron deficiency. VWF activity (VWF:Act) was analyzed using VWF:RCo or VWF:GPIbR. VWF analysis was completed by analysis of VWF multimers and VWF collagen binding (CB) assay (VWF:CB).Results A total of 33 T-MPNs and 18 ST patients were included. Compared with aggregometry, evaluation of VWF:Act by VWF:GPIbR led to lower values in T-MPN patients, but also in ST patients. Interestingly, although the VWF:RCo/VWF:Ag ratio did not reveal differences between T-MPNs and ST patients, the VWF:GPIbR/VWF:Ag ratio analysis allowed us to suspect AVWS only in T-MPN patients. Using the distribution of VWF multimer analysis and VWF:CB, we here demonstrated that VWF:GPIbR allows AVWS diagnosis in nine T-MPNs as opposed to aggregometry.Conclusion Evaluation of VWF:Act using VWF:GPIbR has a greater sensitivity compared with aggregometry to detect AVWS in T-MPN patients.
Keywords: acquired von Willebrand syndrome; myeloproliferative neoplasms; thrombocytosis